A zirconium dioxide-molybdenum ceramic matrix composite based on in-situ reduction and a preparation method thereof

CN122916656APending Publication Date: 2026-10-16HARBIN INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610965315.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-30
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]本发明的目的是为了现有ZrO2-Mo复合陶瓷制备过程中存在的Mo相分布不均、Mo颗粒易团聚、ZrO2/Mo界面接触不充分以及烧结后组织均一性不足的问题,提供一种基于原位还原的ZrO2-Mo纳米复合陶瓷及其制备方法

Benefits of technology

[0023] (1) This invention utilizes a precursor sol-gel process to achieve thorough mixing of ceramic and metal components during the precursor stage; after reduction heat treatment, metallic Mo precipitates in situ on the surface of ZrO2 particles or at the interparticle interface. Compared with traditional mechanical powder mixing methods, this invention significantly reduces the problems of metallic Mo particle agglomeration and local component segregation, achieving in-situ generation and nanoscale uniform dispersion of metallic Mo.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916656A_ABST
    Figure CN122916656A_ABST
Patent Text Reader

Abstract

A zirconium dioxide-molybdenum ceramic matrix composite based on in-situ reduction and a preparation method thereof, the method takes zirconium salt precursor and molybdenum salt precursor as raw materials, realizes in-situ generation and uniform distribution of Mo nano phase in ZrO2 matrix through solution-gel treatment, calcination, reduction heat treatment and rapid sintering densification and other steps. The method first uniformly mixes zirconium salt and molybdenum salt to prepare a composite precursor, obtains a ceramic-metal oxide composite powder through calcination, makes the metal components in-situ reduction to form metal nanoparticles in a reducing atmosphere, and finally prepares a ZrO2-Mo ceramic metal nano composite through spark plasma sintering, hot pressing sintering, hot isostatic pressing sintering or vacuum sintering. Mo in the obtained composite material is uniformly distributed at the ZrO2 grain boundary or intergranular interface, forming a stable ZrO2 / Mo nano interface structure, the average hardness is 13.65±0.87 GPa, the elastic modulus reaches 292.71±12.74 GPa, and 200nm scale microcolumn compression can realize stable deformation of 20%~30%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical fields of ceramic matrix composites, high-temperature structural materials, ultra-high temperature ceramics and metal-ceramic composites. Specifically, it relates to a zirconium dioxide-molybdenum ceramic matrix composite material based on in-situ reduction and its preparation method. In particular, it relates to a method for preparing composite materials by combining solution complexation gel, in-situ reduction and sintering densification to construct a uniformly distributed Mo nanophase and a stable ceramic / metal nano-interface in a ZrO2 matrix. Background Technology

[0002] ZrO2 ceramics possess high melting points, good chemical stability, wear resistance, and high-temperature stability, making them valuable for applications in high-temperature structural components, wear-resistant parts, thermal protection components, and ceramic matrix composites. However, ZrO2 ceramics still exhibit typical brittle characteristics of ceramic materials at room temperature and medium-low temperatures, with limited plastic deformation capacity. They are prone to crack initiation and rapid propagation under external impact, localized stress concentration, or complex force-thermal coupling environments, thus limiting their application in high-reliability structural components.

[0003] Introducing metallic phases into ZrO2 ceramics is an important way to improve their brittle fracture behavior and deformation compatibility. Mo metal has a high melting point, good high-temperature stability, and certain plastic deformation capacity. Introducing the Mo phase into the ZrO2 ceramic matrix is ​​expected to improve the damage tolerance and service reliability of ZrO2 ceramics through crack deflection, interface energy dissipation, stress relaxation, and plastic compatibility.

[0004] Currently, ZrO2-Mo composite ceramics are typically prepared using methods such as mechanical powder mixing, ball milling, and wet mixing followed by sintering. While these methods are simple, they still have significant drawbacks: Firstly, the added Mo powder tends to agglomerate during mixing and sintering, making it difficult to achieve uniform nanoscale dispersion. Secondly, mechanical mixing struggles to achieve uniform molecular or ionic mixing of the ZrO2 and Mo components in the precursor stage, easily leading to localized component segregation, insufficient interfacial contact, and inadequate microstructure uniformity. Furthermore, during traditional sintering, Mo particles tend to grow or aggregate, resulting in uneven distribution at the ZrO2 / Mo interface and hindering the full utilization of the interfacial regulation and plasticity coordination effects of Mo nanoparticles on the ZrO2 ceramic matrix. Summary of the Invention

[0005] The purpose of this invention is to address the problems existing in the preparation of ZrO2-Mo composite ceramics, such as uneven Mo phase distribution, easy agglomeration of Mo particles, insufficient contact at the ZrO2 / Mo interface, and insufficient uniformity of the microstructure after sintering. This invention provides a ZrO2-Mo nanocomposite ceramic based on in-situ reduction and its preparation method. This method achieves uniform mixing of Zr and Mo components through complexation gelation, generates uniformly dispersed Mo nanophases through in-situ hydrogen reduction, and rapidly densifies by spark plasma sintering to suppress Mo phase agglomeration and abnormal grain growth. This results in a ZrO2-Mo nanocomposite ceramic with uniform microstructure, stable interface, and good deformation compatibility.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0007] A zirconium dioxide-molybdenum ceramic matrix composite material based on in-situ reduction, the composite material comprising a ZrO2 ceramic matrix and metallic Mo nanoparticles distributed in the matrix; the metallic Mo nanoparticles are uniformly distributed on the surface of ZrO2 ceramic particles, at the interparticle interfaces, or inside the particle clusters.

[0008] Furthermore, the average particle size of the Mo nanoparticles is 10–200 nm, more preferably 50–100 nm; the average particle size of the ZrO2 ceramic particles is 10–300 nm, more preferably 50–100 nm.

[0009] Furthermore, the mass fraction of the metallic Mo nanoparticles in the composite material is 1–50 wt%, more preferably 5–30 wt%. A stable nano-interface structure is formed between ZrO2 and Mo in the composite material, and Mo is uniformly dispersed, locally coated, interconnected between particles, or distributed in a network state in the ZrO2 matrix.

[0010] A method for preparing the above-mentioned zirconium dioxide-molybdenum ceramic matrix composite material based on in-situ reduction, the method comprising the following steps:

[0011] Step 1: Add zirconium salt, molybdenum salt, and complexing agent to deionized water to form a homogeneous mixed solution, and obtain a precursor solution containing a homogeneous mixture of Zr and Mo components;

[0012] Step 2: Add pH adjuster to precursor solution and age until a gel system is formed to obtain a gel system in which Zr component and Mo component are uniformly mixed;

[0013] Step 3: Dry and calcine the gel system to remove organic components and promote the formation of ceramic phase or ceramic precursor phase to obtain high-temperature ceramic composite precursor powder containing metal oxide or metal compound components.

[0014] Step 4: Heat-treat the precursor powder under a reducing atmosphere to reduce the metal components in situ and precipitate them on the surface of ceramic particles, at the interface between particles or inside the particle clusters to form nano-metal particles, thereby obtaining ZrO2-Mo nanocomposite powder.

[0015] Step 5: The obtained ZrO2-Mo nanocomposite powder is loaded into a mold and sintered and densified in a vacuum, inert atmosphere or reducing atmosphere to obtain ZrO2-Mo ceramic matrix composite material.

[0016] Further, in step one, the zirconium salt is one or more of zirconium oxynitrate, zirconium oxychloride, and zirconium acetate; the reducible molybdenum salt is one or more of ammonium molybdate, ammonium paramolybdate, and ammonium metamolybdate; the complexing agent is one or more of citric acid, oxalic acid, and tartaric acid; and the mass ratio of the zirconium salt, molybdenum salt, complexing agent, and deionized water is 15~30:10~32:50~70:200.

[0017] Further, step two specifically involves: adding 1% to 5% ammonia water to the precursor solution to adjust the pH to 3 to 5, heating and aging at 80 to 100°C for 24 to 48 hours to promote cross-linking of the precursor in the solution and solvent evaporation, resulting in gelation and obtaining a uniformly distributed ZrO2-Mo gel system.

[0018] Further, in step three, the drying temperature is 100~200℃, preferably 100℃, the time is 12~24h, preferably 12h, and the heating rate is 1~10℃ / min, preferably 10℃ / min; the calcination temperature is 500~700℃, preferably 600℃, the holding time is 0.5~6h, preferably 3h, and the heating rate is 1~10℃ / min, preferably 10℃ / min.

[0019] Further, in step four, the reducing atmosphere is a hydrogen-argon mixture, with a hydrogen concentration of 15% to 100%, preferably 100%, i.e., pure hydrogen; the heat treatment temperature is 500 to 1000℃, preferably 800℃, the holding time is 2 to 4 hours, preferably 3 hours, and the heating rate is 5 to 10℃ / min, preferably 5℃ / min.

[0020] Furthermore, in step five, the sintering densification treatment is one of spark plasma sintering or hot pressing sintering.

[0021] Further, in step five, the parameters for the discharge plasma sintering are: sintering temperature of 1000~1500 ℃, sintering pressure of 10~80 MPa, and holding time of 1~10 min; the parameters for the hot pressing sintering are: sintering temperature of 1000~1300 ℃, sintering pressure of 20~50 MPa, and furnace cooling after sintering.

[0022] The advantages of this invention over the prior art are as follows:

[0023] (1) This invention utilizes a precursor sol-gel process to achieve thorough mixing of ceramic and metal components during the precursor stage; after reduction heat treatment, metallic Mo precipitates in situ on the surface of ZrO2 particles or at the interparticle interface. Compared with traditional mechanical powder mixing methods, this invention significantly reduces the problems of metallic Mo particle agglomeration and local component segregation, achieving in-situ generation and nanoscale uniform dispersion of metallic Mo.

[0024] (2) In this invention, the metal Mo particles are not introduced by simply mixing with external metal powder, but are generated in situ on the surface of ZrO2 ceramic particles or between particles. Therefore, the contact between Mo and ZrO2 is more sufficient, which is conducive to forming a stable, continuous and uniformly distributed nano-interface structure.

[0025] (3) Since the obtained ZrO2 particles and Mo particles are both at the nanoscale and are uniformly dispersed, the composite powder has high surface activity and sintering driving force. In the subsequent sintering process, it can promote particle rearrangement, interfacial diffusion and densification process, which is beneficial to obtaining ZrO2-Mo composite materials with uniform structure and good interfacial bonding.

[0026] (4) The present invention uses spark plasma sintering for rapid densification, which can achieve densification of composite powder in a short holding time, suppress the agglomeration and growth of Mo nanoparticles during the sintering process, and improve the uniformity of the structure of composite ceramics.

[0027] (5) In the composite material prepared by the present invention, the metal nanophase can play a role in stress relaxation, crack passivation, crack deflection, crack bridging and interface energy dissipation in the ceramic matrix, which helps to improve the brittle fracture behavior of high temperature ceramic materials and improve the fracture toughness, damage tolerance and plasticity coordination of the composite material.

[0028] (6) The preparation method of the present invention has a clear process flow and adjustable parameters, and is suitable for preparing ZrO2-Mo nanocomposite ceramics with different Mo contents. It can provide a material basis for high-temperature structural parts, impact-resistant components and ceramic matrix composites for extreme environment service. Attached Figure Description

[0029] Figure 1 This is a flow chart of the high-temperature ceramic-metal nanocomposite powder preparation process of the present invention;

[0030] Figure 2 The XRD patterns of the powder after calcination and reduction in Example 1 are shown.

[0031] Figure 3 This is a high-resolution TEM image of the composite powder interface obtained in Example 1;

[0032] Figure 4 Macroscopic image of the bulk material obtained in Example 1;

[0033] Figure 5 High-resolution TEM images of the bulk material obtained in Example 1;

[0034] Figure 6 This is a graph showing the nanoindentation data of the bulk material obtained in Example 1;

[0035] Figure 7 The image shows the compressive stress-strain curve of the nanoscale micropillars of the bulk material obtained in Example 1.

[0036] Figure 8 TEM image of the composite powder obtained in Example 2;

[0037] Figure 9 This is a graph showing the nanoindentation data of the composite material obtained in Example 2. Detailed Implementation

[0038] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0039] This invention achieves thorough mixing of Zr and Mo components at the molecular or nanoscale through uniform solution dispersion and complexation gelation. Subsequently, calcination and reduction heat treatment allow the Mo component to be reduced and precipitated in situ on the surface of ZrO2 particles or at the interparticle interface, resulting in highly dispersed ZrO2-Mo nanocomposite powder. Further densification through sintering yields the ZrO2-Mo composite material. This method enables the formation of a uniformly distributed metallic Mo nanophase and a stable ZrO2 / Mo nano-interface structure within the ZrO2 ceramic matrix, thereby improving the microstructure uniformity, interfacial bonding, and deformation compatibility of the composite material. The specific process is described in [link to detailed process]. Figure 1 .

[0040] This invention utilizes zirconium and molybdenum salt precursors as raw materials, employing steps such as solution-gel treatment, calcination, reduction heat treatment, and rapid sintering densification to achieve in-situ generation and uniform distribution of Mo nanophases within a ZrO2 matrix. The method first involves uniformly mixing zirconium and molybdenum salts to prepare a composite precursor, followed by calcination to obtain a ceramic-metal oxide composite powder. In a reducing atmosphere, the metal components are reduced in situ to form metal nanoparticles. Finally, ZrO2-Mo ceramic-based metal nanocomposite materials are prepared via spark plasma sintering, hot pressing, hot isostatic pressing, or vacuum sintering. In the resulting composite material, Mo is uniformly distributed at ZrO2 grain boundaries or interparticle interfaces, forming a stable ZrO2 / Mo nano-interface structure. The average hardness is 13.65 ± 0.87 GPa, the elastic modulus reaches 292.71 ± 12.74 GPa, and stable deformation of 20%–30% can be achieved under 200 nm micropillar compression. Compared with traditional mechanical powder mixing and sintering processes, this invention achieves in-situ precipitation and uniform distribution of nano-sized Mo metal particles on the surface of ZrO2 particles, which can effectively reduce metal phase agglomeration, improve ceramic / metal interface bonding, and enhance the uniformity of composite material structure, sintering density, fracture toughness, thermal shock resistance and plasticity coordination. It can be applied to high-temperature structural parts, wear-resistant parts, thermal protection components and materials for extreme environment service.

[0041] Example 1:

[0042] (1) Weigh 22.75g of zirconium oxychloride as a ZrO2 precursor and 12.4g of ammonium molybdate as a Mo precursor. Dissolve both in 200g of deionized water and stir to form a transparent or homogeneous mixed solution. Then add 44g of citric acid as a complexing agent to ensure that zirconium ions and molybdate-related components are evenly distributed in the solution.

[0043] (2) Add 5% ammonia to the mixed solution to adjust the pH of the solution to 3, and then heat the resulting mixed solution at 90°C and let it stand for 48 hours until a uniformly distributed ZrO2-Mo gel is formed.

[0044] (3) The gel was dried at 100 °C for 12 h at a heating rate of 10 °C / min to obtain a dry gel. The dry gel was then calcined in air at 600 °C for 3 h at a heating rate of 10 °C / min to remove the organic components and obtain the oxide composite precursor powder. The XRD data after calcination are shown in the figure. Figure 2 As can be seen from the figure, the main components of the calcined powder are zirconium molybdate and zirconium dioxide, at which point the molybdenum compound exists in the form of oxides.

[0045] (4) The calcined composite precursor powder was placed in a 100% hydrogen atmosphere and reduced at 800 °C for 3 h with a heating rate of 5 °C / min to reduce the molybdenum component in situ to Mo nanoparticles, which were then distributed on the surface of ZrO2 particles or at the interparticle interface, thus obtaining ZrO2-Mo nanocomposite powder. The XRD data and morphology of the powder after reduction are shown in [reference needed]. Figure 2 , Figure 3 .from Figure 2 As can be seen, the main components after hydrogen reduction are zirconium dioxide and pure metallic molybdenum. At this point, the molybdenum oxide is fully reduced by hydrogen to obtain metallic molybdenum. From... Figure 3 It can be seen that the zirconium dioxide and molybdenum phases are uniformly distributed, with a particle size of ~50nm, all of which are nanoparticles, and no large particle agglomeration phenomenon is observed.

[0046] (5) The obtained ZrO2-Mo nanocomposite powder was loaded into a graphite mold and densified by spark plasma sintering. The sintering temperature was 1400 ℃, the sintering pressure was 50 MPa, and the holding time was 5 min. Finally, ZrO2-Mo high-temperature ceramic matrix metal nanocomposite material was obtained. The macroscopic image and microstructure of the composite material are shown in […]. Figure 4 , Figure 5 .from Figure 4 It can be seen that the sintered bulk material is macroscopically uniform and dense, without any defects such as voids and cracks visible to the naked eye. From Figure 5 As can be seen, after sintering, the two phases of zirconium dioxide and molybdenum are uniformly distributed at the microscale of the bulk material, with a phase size of ~100nm, still maintaining the nanoscale size, and the two phases have good interfacial bonding to ensure the bonding strength.

[0047] In the obtained material, the Mo metallic phase is uniformly distributed within the ZrO2 ceramic matrix, forming a ceramic / metal nano-interface structure. This is beneficial for improving the material's microstructure uniformity and plasticity coordination. The composite material maintains a nano-hardness of 13.65±0.87 GPa, while possessing an elastic modulus as high as 292.71±12.74 GPa. Furthermore, it can achieve 20% dimensional deformation at the microscale, exhibiting a certain degree of plastic deformation capability. Figure 6 , 7 As shown.

[0048] Example 2:

[0049] (1) Weigh 30g of zirconium acetate solution as ZrO2 precursor and 12.4g of ammonium molybdate as Mo precursor, dissolve them in 200g of deionized water, and stir them to form a transparent or homogeneous mixed solution. Then add 50g of citric acid as a complexing agent to make zirconium ions and molybdate-related components uniformly distributed in the solution.

[0050] (2) Add 5% ammonia to the mixed solution to adjust the pH of the solution to 4, and then heat the resulting mixed solution at 100°C and let it stand for 48 hours until a uniformly distributed ZrO2-Mo gel is formed.

[0051] (3) The gel was dried at 120 °C for 12 h with a heating rate of 10 °C / min to obtain a dry gel. The dry gel was then calcined in air at 500 °C for 4 h with a heating rate of 10 °C / min to remove the organic components and obtain oxide composite precursor powder.

[0052] (4) The calcined composite precursor powder was placed in 20% hydrogen gas and reduced at 900 °C for 3 h to reduce the molybdenum component in situ to Mo nanoparticles, which were then distributed on the surface of ZrO2 particles or at the interparticle interface, thus obtaining ZrO2-Mo nanocomposite powder. The morphology of the powder is shown in the figure. Figure 8 As can be seen from the figure, the powders obtained in Example 2 and Example 1 have almost the same particle size, which indicates that using different precursor raw materials has almost no effect on the final morphology of the powder.

[0053] (5) The obtained ZrO2-Mo nanocomposite powder was loaded into a graphite mold and densified by spark plasma sintering. The sintering temperature was 1300 ℃, the sintering pressure was 60 MPa, and the holding time was 5 min, finally obtaining ZrO2-Mo high-temperature ceramic matrix metal nanocomposite material.

[0054] In the obtained material, the Mo metallic phase is uniformly distributed within the ZrO2 ceramic matrix, forming a ceramic / metal nano-interface structure. This is beneficial for improving the material's microstructure uniformity and plasticity coordination. The composite material maintains a nano-hardness of 13.29±0.54 GPa while possessing an elastic modulus as high as 283.70±5.67 GPa. Figure 9 As shown.

Claims

1. A zirconium dioxide-molybdenum ceramic matrix composite material based on in-situ reduction, characterized in that: The composite material includes a ZrO2 ceramic matrix and metallic Mo nanoparticles distributed in the matrix; the metallic Mo nanoparticles are uniformly distributed on the surface of ZrO2 ceramic particles, at the interparticle interfaces, or inside the particle clusters.

2. The zirconium dioxide-molybdenum ceramic matrix composite material based on in-situ reduction according to claim 1, characterized in that: The average particle size of the Mo nanoparticles is 10–200 nm, and the average particle size of the ZrO2 ceramic particles is 10–300 nm.

3. The zirconium dioxide-molybdenum ceramic matrix composite material based on in-situ reduction according to claim 1, characterized in that: The mass fraction of the metallic Mo nanoparticles in the composite material is 1–50 wt%.

4. A method for preparing the zirconium dioxide-molybdenum ceramic matrix composite material based on in-situ reduction as described in any one of claims 1 to 3, characterized in that: The method includes the following steps: Step 1: Add zirconium salt, molybdenum salt, and complexing agent to deionized water to form a precursor solution; Step 2: Add a pH adjuster to the precursor solution and age until a gel system is formed to obtain the gel system; Step 3: Dry and calcine the gel system to obtain precursor powder; Step 4: Heat-treat the precursor powder under a reducing atmosphere to obtain ZrO2-Mo nanocomposite powder; Step 5: The obtained ZrO2-Mo nanocomposite powder is loaded into a mold and sintered and densified in a vacuum, inert atmosphere or reducing atmosphere to obtain ZrO2-Mo ceramic matrix composite material.

5. The preparation method according to claim 4, characterized in that: In step one, the zirconium salt is one or more of zirconium oxynitrate, zirconium oxychloride, and zirconium acetate; the molybdenum salt is one or more of ammonium molybdate, ammonium paramolybdate, and ammonium metamolybdate; the complexing agent is one or more of citric acid, oxalic acid, and tartaric acid; and the mass ratio of the zirconium salt, molybdenum salt, complexing agent, and deionized water is 15~30:10~32:50~70:

200.

6. The preparation method according to claim 4, characterized in that: Step two specifically involves adding 1% to 5% ammonia water to the precursor solution to adjust the pH to 3 to 5, heating and aging at 80 to 100°C for 24 to 48 hours to obtain a uniformly distributed ZrO2-Mo gel system.

7. The preparation method according to claim 4, characterized in that: In step three, the drying temperature is 100~200℃, the time is 12~24h, and the heating rate is 1~10℃ / min; the calcination temperature is 500~700℃, the holding time is 0.5~6h, and the heating rate is 1~10℃ / min.

8. The preparation method according to claim 4, characterized in that: In step four, the reducing atmosphere is a hydrogen-argon mixture with a hydrogen concentration of 15% to 100%, the heat treatment temperature is 500 to 1000°C, the holding time is 2 to 4 hours, and the heating rate is 5 to 10°C / min.

9. The preparation method according to claim 4, characterized in that: In step five, the sintering densification treatment is one of spark plasma sintering or hot pressing sintering.

10. The preparation method according to claim 4 or 9, characterized in that: In step five, the parameters for the discharge plasma sintering are: sintering temperature of 1000~1500 ℃, sintering pressure of 10~80 MPa, and holding time of 1~10 min; the parameters for the hot pressing sintering are: sintering temperature of 1000~1300 ℃, sintering pressure of 20~50 MPa, and furnace cooling after sintering.